Lingkungan Kerja Sosial Dan Pengembangan Karir Sebagai Pengaruh Kepuasan Kerja Karyawan - Maharani, Nadia; Sumiyati, Sumiyati; Masharyono, Masharyono (Universitas Pendidikan Indonesia, 2019)
The purpose of this research was to see how much influence the social work environment and career development had on employee job satisfaction. Type of Research Methodology used is descriptive verification. The method used is explanatory survey with simple random sampling technique and the number of samples is 102 respondents. The data analysis technique used is multiple linear regression with SPSS 21.0 computer software tools. The findings based on the results of the study can be seen that simultaneously or partially the social work environment and career development can improve employee job satisfaction. The difference in this study lies in the research object, research time, measuring instruments, literature used, the theory used and the results of the study.